The role of standards in Hospitals’ buildings adaptation - Mustafa Kamil Kadhim; Rasha Noori Ahmed (Iraqi Journal of Architecture and Planning, 2018)
Previous studies have shown adaptation as key requirements of 21st century buildings generally and particularly, in hospitals’ buildings design, which are depend to apply the technical and global standards enable them to keeping up the development, and be respond to all changes happened with the evolution. While the war and the security deterioration are important factors that effect of hospital performance largely, and make it to exposure the functional and spatial obsolescence, and through that the research was founded lack of studies that focused on the concept of adaptation in the healthcare facilities, that identified theproblem as (Lack of studies which deal with the concept of adaptation in local hospital buildings), and shown the hypothesis as (the buildings of hospitals designed according to VA standards, are adaptive buildings to any change occurs). So the research was elected al-Falluja Teaching Hospital as a local sample in practical study, that leading to the criteria of structural building are the most important criteria achieving adaptation in hospital buildings.